The San Francisco Declaration (DORA) and bad bibliometrics - Aguillo, Isidro F (Anuario ThinkEPI, 2015)
The San Francisco Declaration on Research Assessment (DORA) not only criticizes the misuse of Garfield´s impact factor as a tool for the evaluation of scientific activity, but implicitly questions citation analysis in particular and bibliometric practice in general. The work of the professional bibliometric community is defended, identifying technical errors and commercial practices of the companies providing bibliometric data, which are largely responsible for the structural problems, while warning of a conjunctural situation that results from the generalization of "easy bibliometrics". This situation should be corrected with a future statement of good practice now under development by a group of bibliometrists.